Broadband coherently synthesized two-color electro-optic frequency combs with phase noise suppression. (1st January 2023) - Li, Runmin; Tian, Haochen; Kato, Takashi; Asahara, Akifumi; Minoshima, Kaoru
Abstract: A coherently synthesized 1550/1560 nm two-color EO comb is generated by modulating two continuous-wave lasers with common EO modulators and phase-locking their beat note. Compared with a single-color EO comb, the phase noise of comb modes that accumulated from the RF synthesizer is effectively suppressed in our coherently synthesized two-color EO comb. Besides, a broader spectrum is demonstrated in a coherently synthesized 1535/1560 nm two-color EO comb, with a 60-nm total spectrum span. The coherently synthesized two-color EO combs are expected to be applied in coherent communication, spectroscopy, absolute distance measurement, etc.